Alcoholism, Korsakoff’s Syndrome and the Frontal Lobes - R. R. Jacobson (Behavioural Neurology)
A subset of the diffuse cerebral changes and psychometric deficits found in chronic alcoholics is similar to that seen in the frontal lobe syndrome. Certain features of alcoholic Korsakoff's syndrome (AKS) also point to cortical involvement, and this may have a basis in alcohol neurotoxicity. Twenty-five patients with AKS and 24 non-Korsakoff alcoholic controls were compared using an automated CT brain scan program. In addition to evidence of their diencephalic lesions (wide third ventricles), AKS patients revealed widespread cerebral damage with greater Sylvian and interhemispheric fissure (IHF) size than alcoholics. Korsakoffs were also inferior to alcoholics in performance on a category sorting test, in which non-perseverative error scores correlated significantly with IHF size. The principle of distinguishing between selective memory decline and global intellectual decline (GID) was applied to 38 patients with AKS. Indices were developed for each type of deficit and much variation found in their distributions. The degree of GID correlated significantly with IHF size, showing similar trends with other cortical measures. These results suggest a cortical substrate for the degree of GID and a frontal substrate for category sorting deficits; with a probable basis in alcohol neurotoxicity rather than thiamine deficiency, which is not known to impair cortical structure. A new model is proposed of the pathophysiology of alcoholic brain damage and AKS which includes recent work on neurotransmitter sources and thalamo-frontal connections.